1996
DOI: 10.1007/bf02943098
|View full text |Cite
|
Sign up to set email alerts
|

The effects of therapy with rifampicin and isoniazid on basic investigations for Cushing’s syndrome

Abstract: Rifampicin(R) is a potent enzyme inducer which is now widely used to treat many conditions. We have investigated its effect on adrenal function tests in 18 adults with tuberculosis on rifampicin (R) and isoniazid (INH) as in-patients. Midnight cortisol was above 250 nmol/l in 11 patients with a mean +/- (SD) of 340 +/- 193 nmol/l. The morning serum cortisol following 1 and 4 mg dexamethasone overnight was abnormal in 88.9 per cent and 83.3 per cent respectively. The respective mean values +/- (SD) were 350 +/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Interestingly, the current best SXR activator, rifampicin, is also known to be involved in numerous drug-drug interactions as a consequence of drastically altering their metabolism by inducing CYP3A4. Thus, long-term rifampicin therapy for tuberculosis also increases steroid clearance, in some cases leading to a misdiagnosis of Cushing's syndrome (Kyriazopoulou and Vagenakis 1992;Terzolo et al 1995;Zawawi et al 1996). In patients with Addison's disease, who are on steroid replacement therapy, or women taking oral contraceptives, rifampicin treatment leads to rapid depletion of administered steroids, confirming that induction of CYP3A4 causes increased steroid catabolism as predicted by the model (Edwards et al 1974;Kyriazopoulou et al 1984).…”
Section: Sxr-a Steroid and Xenobiotic Sensormentioning
confidence: 68%
“…Interestingly, the current best SXR activator, rifampicin, is also known to be involved in numerous drug-drug interactions as a consequence of drastically altering their metabolism by inducing CYP3A4. Thus, long-term rifampicin therapy for tuberculosis also increases steroid clearance, in some cases leading to a misdiagnosis of Cushing's syndrome (Kyriazopoulou and Vagenakis 1992;Terzolo et al 1995;Zawawi et al 1996). In patients with Addison's disease, who are on steroid replacement therapy, or women taking oral contraceptives, rifampicin treatment leads to rapid depletion of administered steroids, confirming that induction of CYP3A4 causes increased steroid catabolism as predicted by the model (Edwards et al 1974;Kyriazopoulou et al 1984).…”
Section: Sxr-a Steroid and Xenobiotic Sensormentioning
confidence: 68%
“…Interestingly, the PXR transgenic mice exhibited normal ACTH secretion in pituitary, and intact suppression of dexamethasone by corticosterone, indicating a functionalhypothalamus-pituitary-adrenal axis in spite of severely disrupted adrenal steroidhomeostasis. Consistent with these observations, several clinical studies reported that rifampicin increased steroid secretion in urine and may have resulted in misdiagnosis of Cushing’s syndrome [118, 119]. Therefore, PXR has a potential to disrupt endocrine homeostasis, and it may be broadly implicated in drug-hormone interactions.…”
Section: Pxr In Endobiotic Metabolismmentioning
confidence: 73%
“…When synthetic steroids, such as prednisolone (McAllister et al 1983;Lee et al 1993) or 17␣-ethynylestradiol (Guengerich 1990) are administered together with rifampicin, plasma levels are rapidly decreased due to enhanced urinary clearance. In some patients undergoing rifampicin therapy for tuberculosis, the increase in urinary steroid levels has led to misdiagnosis of Cushing's syndrome (Kyriazopoulou and Vagenakis 1992;Terzolo et al 1995;Zawawi et al 1996). Steroid production and clearance normalized when rifampicin was withdrawn.…”
Section: Discussionmentioning
confidence: 99%